My Neighbor Next Floor: The Built Environment and Social Preferences - Castillo, Marco; Petrie, Ragan; Rong, Rong (The Review of Economics and Statistics, 2025)
Abstract We assess the effect of the built environment on low-cost helping behavior toward neighbors. The setting is households in Shanghai, China that, due to rapid development, were involuntarily, i.e. as good as randomly, relocated to different building structures. Using a natural field experiment of misdelivered mail, we test the causal effect of spatial proximity and the built environment on helping behavior. Living one floor apart reduces the willingness to help a neighbor by 16 percentage points, similar to adding one more apartment per floor. Small spatial barriers can profoundly shape social interactions, and helping behavior, in urban settings.